The Making of Biobriquettes with Carbonization Method by Utilizing Sludge Cake and Wood dust from the Pulp Industry - Lintang Alnasyah, Masnun; Renilaili; Kusmindari, Ch. Desi; Pasmawati, Yanti; AR, Hasmawaty (International Journal of Scientific Research and Management (IJSRM), 2024)
Sludge cake as a solid waste that is rarely used from residual sludge from Waste Water Treatment Plants is one source of biomass from the pulp and paper industry which has the potential to be used as renewable energy. Analysis of biobriquette characteristics includes: moisture content, ash content, volatile matter, bound carbon, and calorific value. The results of this research show that the best combination of biobriquettes is biobriquettes with a composition of 40% sludge cake, 50% Eucalyptus pellita wood dust, and 10% black liquor adhesive which has a moisture content of 2.12%, ash content of 19.33%, volatile matter 28 .99%, calorific value of 4915.69 kJ/gr, and fixed carbon content of 49.63%.